Sustainable Palestine Solidarity: WatermelonSymbols, Boycotts and Muslim Micro Celebritieson Instagram - Fathurrahman; Fahrurrozi; Abdul Wahid; Ahmad Amir Aziz (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
Users of social media platforms communicate various forms and symbols of support for Palestine, such as the symbol of watermelon which has its own meaning as a form of support for the state of Palestine. This research uses a qualitative approach with the library research method and a qualitative descriptive approach, where the researcher will further explore the symbolic communication of watermelon, both the meaning behind the symbol which is used as a form of defense of the Palestinian state, then the impact of the boycott action, and this research wants to look at the existence of the Micro celebrities attract sympathy on social media.